0359 Systematic review of occupational chemical exposures and cardiovascular diseases. (21st August 2017) - Hogstedt, Christer; Albin, Maria; Hall, Charlotte; Sjögren, Bengt; Theorell, Töres
Abstract : Background: A systematic review of the associations between occupational chemical exposures and cardiovascular diseases has been performed under management of Swedish Agency for Health Technology Assessment and Assessment of Social Services (SBU). Methods: Inclusion criteria: (i) epidemiology publication in English in peer-reviewed journal between 1970 and 2016, (ii) cohort studies with at least 50 exposed participants or case-control studies with at least 50+50 participants. Relevance and quality were assessed using predefined criteria. Level of evidence was assessed using the GRADE system. Consistency of findings was examined for a number of confounders and regarding the healthy worker effect when possible. Results: More than 8000 abstracts were screened. 162 articles of high or medium high scientific quality were finally included. There was moderately strong evidence (grade 3 out of 4) for a relationship between silica dust, engine exhaust and welding and IHD incidence. Limited evidence (grade 2) was found for arsenic, benz(a)pyrene, lead, dynamite, carbon disulphide, carbon monoxide, cutting fluids, TCDD, asbestos and tobacco smoke in the work environment. Results for stroke, cor pulmonale and high blood pressure will also be reported. Conclusions: This review identified several established associations, some less established and many knowledge gaps including lack of studies on women. Many chemical exposures have not been studied epidemiologically and there is often a shortage of exposure estimates, particularly concerning intensity and long-term exposure. A comprehensive risk analysis of chemical exposures must use social, environmental and experimental results as well.